The study of the Relationships of Microcystis aeruginosa to the Geographically Diverse Distribution - Jaiswal, Kailash Prasad; Gothalwa, Ragini; Yadav, A.S. (International Journal of Scientific Research in Biological Sciences, 2022)
Cyanobacteria blooms occurred worldwide, including in India Microcystis aeruginosa is a cyanotoxins producing species that occurs in aquatic habitats such as lakes and rivers and varies with different geographical locations. Microcystin (Hepatotoxin) causes serious health hazards in humans, animals, and aquatic living organisms. The ability of microcystin to inhibit the growth of cancer cell lines may lead to the discovery of effective anticancer drugs, pharmacological and toxicological significance of the cyanobacterial genera Microcystis. The influence of nutritional, physicochemical, and environmental factors had effects on the release of microcystin (Hepatotoxin) in Microcystis aeruginosa in different aquatic environments of central India. In this study, we investigated the distribution of potentially-toxic Microcystis aeruginosa for environmental factors that influence the abundance of Microcystis aeruginosa cell density in lakes, dams, and rivers of different aquatic regions (Bhopal, Ujjain, Tikamgarh, Gwalior, and Rewa) of central India. Microcystis aeruginosa populations were found in 97.5% of the sites, with the number of cells peaking in the rainy season (7.3 x 106 cells L?1), followed by similar trends in the winter season (6.1 x 106 cells L?1), and a significant decrease in the summer (4.2 x 106 cells L?1). Seasonal significant differences were observed in the rainy (p>0.07), winter (p>0.05) and summer (p>0.02) seasons in Microcystis aruginosa. Thus, a significant difference in microcystin-producing Microcystis aeruginosa cells and Chl-concentrations throughout the year, correlating with these various biological and physicochemical parameters, confirms the importance of local environmental factors like phosphorus, nitrate, DO concentration, and pH, as well as regional conditions like distance from built areas and nature reserve parameters, in influencing the geographical distribution of toxigenic Microcystis. Furthermore, the results show that microcystin identified the pharmacological importance of the cyanobacterial genera Microcystis aeruginosa.